Analisis Didaktik Pembelajaran yang Dapat Meningkatkan Korelasi antara Pemahaman Konsep dan Kemampuan Pemecahan Masalah Siswa SMA pada Materi Fluida Dinamis - Fathiah Fathiah; Ida Kaniawati; Setiya Utari (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
AbstrakThe background study of the results of discussions with the teacher, the initial data in the form of cognitive ability tests and observations in class about the problem often encountered in physics related to fluid dynamic learning. Problems arise, among others: the student has understood the concept, but less able to use the concept of understanding in solving problems in the real life of the related phenomena. Students tend to capture about a matter but are less able to solve problems related to fluid dynamic phenomena are real. This is due to the fluid dynamic learning material physics that took place in the school they are informative and abstract, tend to be more emphasis on the formulation of mathematical equations, as well as less engaging students in interacting directly with real phenomena. This study aims to develop a fluid dynamic design of learning materials to improve the correlation between the understanding of concepts and problem solving skills based on the analysis of hypothetical learning trajectory (HLT) on cognitive abilities of students. Descriptive study was conducted on 30 students in one of the high schools in the district of Tangerang. The results of the study provide information for further research studies in the development of the hypothesized didactic design can enhance the understanding of the concept of correlation between the problem solving ability of students to the dynamic fluid material.Keywords: Hypothetical Learning Trajectory, didactic design, understanding of concepts, problem solving abilities, dynamic fluidAbstrakKajian ini dilatarbelakangi dari hasil diskusi dengan guru, data awal berupa tes kemampuan kognitif dan pengamatan di kelas tentang masalah yang sering dihadapi dalam pembelajaran fisika terkait fluida dinamis. Masalah yang muncul antara lain: siswa telah memahami konsep, namun kurang mampu menggunakan pemahaman konsepnya tersebut dalam memecahkan masalah di kehidupan nyata tentang fenomena terkait. Siswa cenderung menguasai soal hitungan tapi kurang mampu memecahkan masalah terkait fenomena fluida dinamis yang riil. Hal ini disebabkan pembelajaran fisika materi fluida dinamis yang berlangsung di sekolah masih bersifat informatif dan abstrak, cenderung lebih ditekankan pada perumusan persamaan matematis, serta kurang melibatkan siswa dalam berinteraksi langsung dengan fenomena nyata. Penelitian ini bertujuan untuk mengembangkan desain pembelajaran materi fluida dinamis yang dapat meningkatkan korelasi antara pemahaman konsep dan kemampuan pemecahan masalah berdasarkan hasil analisis hypothetical learning trajectory (HLT) terhadap kemampuan kognitif siswa. Penelitian deskriptif dilakukan pada 30 siswa di salah satu SMA Negeri di Kabupaten Tangerang. Hasil penelitian memberikan informasi untuk kajian penelitian selanjutnya dalam upaya pengembangan desain didaktik yang dihipotesiskan dapat meningkatkan korelasi antara pemahaman konsep dengan kemampuan pemecahan masalah siswa pada materi fluida dinamis.Kata-kata kunci: Hypothetical Learning Trajectory, desain didaktik, pemahaman konsep, kemampuan pemecahan masalah, fluida dinamis